A study of electrode shape configuration on the performance of die sinking EDM - Khan, Ahsan Ali; Ali, Mohammad Yeakub; Haque, Md. Mohafizul (Universiti Malaya, 2009)
This paper discusses the performance of die sinking EDM due to the shape configuration of the electrode. The effect of electrode shape on material removal rate (MRR), electrode wear rate (EWR), wear ratio (WR), and average surface roughness (Ra) has been investigated for mild steel work material and copper electrode. The shapes of the electrodes were round, square, triangular, and diamond of constant cross-sectional area of 64 mm2. Experiments were repeated for three current values of 2.5, 3.5, and 6.5 A. The highest MRR was found for round electrodes followed by square, triangular and diamond shaped electrodes. However, the highest EWR and WR were found for the diamond shaped electrodes. The minimum surface roughness was found for the round electrodes followed by square, triangular and diamond shaped electrodes. However, the influence of the shape of the electrodes on surface roughness was found to be insignificant.